SUBCRITICAL COMPACTION AND YIELDING OF GRANULAR QUARTZ SAND - Karner S.L.; Chester F.M.; Kronenberg A.K.; Chester J.S. (My University, 2003)
Cylindrical samples of water-saturated, initially loose, St. Peter quartz sand were consolidated using triaxial deformation apparatus at room temperature, constant fluid pressure (12.5 MPa), and elevated confining pressures (up to 262.5 MPa). The samples were deformed along four loading paths: (1) hydrostatic stressing tests in which confining pressure was monotonically increased; (2) hydrostatic stress cycling similar to (1) except that effective pressure was periodically decreased to initial conditions; (3) triaxial deformation at constant effective pressure in which differential stress was applied after raising effective pressure to an elevated level; and (4) triaxial stress cycling similar to (3) except that the axial differential stress was periodically decreased to zero. Hydrostatic stressing at a constant rate results in a complex nonlinear consolidation response. At low pressures, large strains occur without significant acoustic emission (AE) activity. With increased pressure, the stress versus strain curve becomes quasi-linear with a corresponding nonlinear increase in AE rates. At elevated pressures, macroscopic yielding is marked by the onset of large strains, high AE rates, and significant grain failure. Stress cycling experiments show that measurable inelastic strain occurs at all stages of hydrostatic loading. The reload portions of stress cycles are characterized by a poro-elastic response and lower AE rates than during constant rate hydrostatic stressing. As the stress nears and exceeds the level that was applied during previous loading cycles, strain and AE rates increase in a manner consistent with yielding. Triaxial stressing cycles achieve greater consolidation and AE rates than hydrostatic loading at similar mean stress levels. By comparing our results with previously published studies, we construct a three-component model to describe elastic and inelastic compaction of granular sand. This model involves acoustically silent grain rearrangement that contributes significant inelastic strain at low pressures, poro-elastic (Hertzian) deformation at all pressures, and inelastic strain related to granular cracking and particle failure which increases in significance at greater pressures.
Keywords: COMPACTION; DEFORMATION; FLOW; FRACTURE; SAND; SEDIMENTARY